Pengaruh Program Flash Sale terhadap Perilaku Impulsive Buying Konsumen Marketplace - Dermawansyah Darwipat; Agus Syam; Marhawati (Journal of Economic Education and Entrepreneurship Studies, 2020)
This study aims to determine the effect of flash sales on the impulsive buying behavior of marketplace consumers in women. This research is categorized as a quantitative descriptive study with a simple regression approach. The population in this study were 347 female students, and a sample of 54 female students was obtained. Data collection was carried out using observation, documentation and questionnaire techniques. The analysis technique used is simple linear regression. The results of this study indicate that the survey conducted on students of the Department of Economics education resulted in the conclusion that flash sales have a significant effect on impulsive buying.